Qualification and competences: the permanent validation of the worker - Godoy Stenico, Joselaine Andreia de [UNESP]; Adam, Joyce Mary [UNESP] (Centro Univ La Salle, 2017)
This paper presents some propositions about the qualifications for the job, demonstrating the development of theoretical construction from Friedmann (1973 and 1983) and Naville (1956, 1973 and 1973a), furthermore, identifies the qualification in the context of the 21st century. The research took a qualitative approach, guided by critical evaluation systematic literature. Among the results obtained, it is worth noting that the idea of qualification does not seem to be more sufficient, it is imperative to hold professional skills that allow solving with effectiveness a number of situations within the company.
Keywords: Qualification; Skills; Friedmann and Naville